The Relevance of the Concept of Justice in Islamic Law to Contemporary Humanitarian Issues - Karimullah, Suud Sarim (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This study explores the relevance of the concept of justice in Islamic law to complex and urgent contemporary humanitarian problems. Through the method of literature study with integrative and comprehensive literature analysis, this research conducts in-depth and structured investigations of existing literature to summarize and synthesize relevant views, arguments, findings, and thoughts. The results of the study stated that the concept of justice in Islamic law is a central aspect in Islamic religious teachings and has wide application in facing various humanitarian challenges today. Through a deep understanding of the concept of justice in Islamic law, societies can form solid moral views and act effectively to advance human rights, address economic disparities, facilitate peace, and respond to other humanitarian issues. This makes it possible to view the concept of justice in Islamic law not only as a religious aspect but also as a potential source of inspiration to build a more just and sustainable world for all humanity, whatever their religious or cultural background.